2016
DOI: 10.1002/hed.24563
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique of creating a seal for the vacuum‐assisted closure system application in complex head and neck wounds

Abstract: A green glove technique allows for a good seal for the VAC system to work, especially when applied to complex head and neck wounds. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2523-E2526, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…VAC systems can be a useful adjunct to therapy to prevent the pooling of sinus secretions in the neck and to achieve closure of potential spaces. These systems have been used with increasing frequency in the management of head and neck wounds . VAC systems effect wound healing by increasing granulation tissue formation via three proposed mechanisms: increasing local blood flow, removal of factors that inhibit wound healing, and alternating mechanical stress on the cells at the wound surface .…”
Section: Discussionmentioning
confidence: 99%
“…VAC systems can be a useful adjunct to therapy to prevent the pooling of sinus secretions in the neck and to achieve closure of potential spaces. These systems have been used with increasing frequency in the management of head and neck wounds . VAC systems effect wound healing by increasing granulation tissue formation via three proposed mechanisms: increasing local blood flow, removal of factors that inhibit wound healing, and alternating mechanical stress on the cells at the wound surface .…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck fistula tends to occur following extensive resection for cancer, with a reported incidence ranging from 3-65% [29]. In a recent study in which almost all of the included cases were oral lesions (e.g., cancer, osteoradionecrosis, or ameloblastoma), the incidence of orocutaneous fistula following head and neck reconstructive surgery was 10% [30].…”
Section: Discussionmentioning
confidence: 99%
“…Referenced studies using NPWT for fistulae all include radiated patients; 29 of 61 total patients. 8 32 33 34 35 36 37 However, only Inatomi et al stratified patients by history of radiation and they surprisingly showed that there was no significant difference in resolution rate. 34 The accepted, speculated mechanism of action of NPWT for resolution of head and neck fistulae is that, when sponge is placed near the superficial aspect of the fistula tract, the negative pressure results in the walls of the fistula collapsing and opposing one another resulting in eventual seal.…”
Section: Negative Pressure Wound Therapy For Head and Neck Fistula Ma...mentioning
confidence: 99%
“…Complete healing with NPWT alone was achieved in 61.8% of patients, while 34.5% underwent additional procedures with adjuvant tissue transfer. 11 A majority (79.1%) of treated wounds in their series were deemed complex due to: salivary contamination (64), bone exposure (40), exposure of great vessels (25), following free tissue transfer (55), and peristomal wounds following laryngectomy (32). Indeed, other authors have shown the effectiveness of NPWT in the head and neck in similar austere settings that arise after complex tumor ablation and defect reconstruction.…”
Section: Effectiveness In Head and Neck Woundsmentioning
confidence: 99%